Academic recovery : supporting students in academic probation - Dial, Michael T., 1986- (Columbia, SC : National Resource Center for The First-Year Experience® and Students in Transition, 2022)
"An academic resource for higher education professionals that provides guidance on how to better support students who are in endanger of or are on academic probation."--
What we know about students on probation and supporting them / Michael T. Dial -- Institutional policies on probation, dismissal, and reinstatement / Caleb Morris & Andrea Harris -- Advising students on probation / Catherine Nutter -- Coaching students on probation / Claire Robinson -- Early alert and academic intervention / Michael T. Dial & Paige McKeown -- First-year seminars for students on academic probation / Dan Friedman, Stephanie M. Foote, & Dottie Weigel -- Assessing programs aimed at supporting first-year students on probation / Dallin George Young & Dottie Weigel -- Intentionality and integration within academic probation policies and programs / Richie Gebauer & Michael T. Dial.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 09, 2023).
eBooks on EBSCOhost
Keywords: Counseling in higher education; College attendance; Academic achievement; College students -- Rating of; Effectifs étudiants.; Étudiants -- Évaluation.; Academic achievement; College attendance; College students -- Rating of; Counseling in higher education